Gaya Lateral In-Plane Struktur Portal Dinding Pasangan Bata ½ Batu Melalui Analisis Numerik - Prayuda, Hakas (Semesta Teknika, 2015)
Building construction in Indonesia is categorized as two big classes; there are engineered building and non-engineered building. Non-engineered building is very susceptible to the lateral load such as an earthquake, either medium earthquake or massive earthquake that causing sudden collapse so that the research of mitigation building strength needs to be done which is rely on the strength of brick masonry (non-engineered building) that can be predicted through measuring micro vibration at the bottom and the top of the brick masonry wall surface. The aims of this research is to find out the effect of ½ stone brick masonry in its contribution to the rigidity of simple portal structure by using loading in-plane lateral system. Loading analysis result at the plastic limit is 95, 524 kN or only 86,89% of the maximum load, meanwhile lateral deviation at the plastic limit is 7,506 cm or 27,51% of maximum lateral deviation. Besides, The rigidity of ½ stone brick masonry wall is 12,72 kN/cm.